Synthesis of 2RS,4RS-1-[2-Phenyl-4-[2-(2-trifluromethoxy-phenoxy)-ethyl]-1,3-dioxolan-2-yl-methyl]-1H-1,2,4-triazole Derivatives as Potent Inhibitors of Brassinosteroid Biosynthesis - Yuko Yoshizawa; Kazuhiro Yamada; Keimei Oh (Molecules, 2012)
Brassinosteroids are important phytohormones that affect many aspects of plant growth and development. In order to manipulate brassinosteroid levels in plant tissues by using specific biosynthesis inhibitors, we have carried out a systemic search for specific inhibitors of brassinosteroid biosynthesis. Synthesis of triazole derivatives based on the ketoconazole scaffold revealed a series of novel brassinosteroid biosynthesis inhibitors (the YCZ series). To explore the structure-activity relationships of this synthetic series, we now report the synthesis of new triazole derivatives with different aromatic structures at position 2 of 1,3-dioxolane skeleton. We found that the variation of aromatic substituent significantly affect the inhibitory potency. Structure-activity relationships studies indicated that 4-chlorophenyl analogue is the most potent inhibitor of BR biosynthesis with an IC50 value approximately 0.12 ± 0.04 µM, while a bulky biphenyl group exhibited a great negative effect on promoting the inhibitory potency with an IC50 larger than 10 µM.